Soil Improvement Planning Combination of Preloading and Stone Column (Case Study) in Sidorukun District, Gresik, Jawa Timur - Kusumaningrum, Dewi; Sri Utami, Gati; Catur Atmaja, Johan (Jurnal IPTEK, 2021)
The subgrade is the essential part of the construction process, such as access to factories, to develop industrial factory in areas to be developed, one of which in the Gresik area. Not all construction site has met the requirement. Hence, need soil improvement with a combination of preload and stone column. The soil parameters show the results of field and laboratory tests that the area has a small value NSPT with a thickness of the soft bottom layer up to a depth of 20 meters. This research is planned the initial height (Hinitial) to have stability analysis of un-reinforcement embankment, the diameter, and the distance from the stone column with the Xstab program. The results of the calculations carried out for the construction height of the embankment (Hfinal) 3.50 meters, then the first dam (HInitial) of 4.60 m is required. The tilt stabilization is obtained (MR = 168.7 tonm), wherein The Radius of the Slope area is 11.62 meters and the Safety Factor (SF = 0.881), where there is a possibility to slide. Planning preload with a stone column with a diameter of 1.00 meters needs to be combined, a distance of 1.50 meters installed in the subgrade.